Hilbert transform analysis of a time series of speckle interferograms with a temporal carrier - Marengo Rodriguez, Fernando Alberto (2008)
We present an optical phase measurement method based on the Hilbert transform for the analysis of a time series of speckle interferograms modulated by a temporal carrier. We discuss the influence of non-modulating pixels, modulation loss, and noise that affect the bias and modulation intensities of the interferometric signal and propose the application of the Empirical Mode Decomposition method for its minimization. We also show the equivalence between the phase recovery approaches that are based on the Hilbert and the Fourier transforms. Finally, we present a numerical comparison between these methods using computer-simulated speckle interferograms modulated with a temporal carrier.